2018
DOI: 10.1016/j.bbalip.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase-2 is a lipid-modulated modulator of muscular lipid homeostasis

Abstract: There is a growing body of evidence that poly(ADP-ribose) polymerase-2 (PARP2), although originally described as a DNA repair protein, has a widespread role as a metabolic regulator. We show that the ablation of PARP2 induced characteristic changes in the lipidome. The silencing of PARP2 induced the expression of sterol regulatory element-binding protein-1 and -2 and initiated de novo cholesterol biosynthesis in skeletal muscle. Increased muscular cholesterol was shunted to muscular biosynthesis of dihydrotest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 69 publications
(78 reference statements)
1
30
0
Order By: Relevance
“…PARPs interfere with hormonal signaling at various points. PARPs regulate hormone levels, including intramuscular androgen production (Marton et al 2018b). Fasting serum insulin levels were lower in PARP2 knockout mice (Bai et al 2011a), weak PARP inhibitors were shown to restore insulin expression (Ye et al 2006) and the deletion of Tankyrase 1 (PARP5a, TNK1) induced serum insulin levels (Yeh et al 2009).…”
Section: Parps In Regulating Central and Peripheral Organismal Metabomentioning
confidence: 99%
See 4 more Smart Citations
“…PARPs interfere with hormonal signaling at various points. PARPs regulate hormone levels, including intramuscular androgen production (Marton et al 2018b). Fasting serum insulin levels were lower in PARP2 knockout mice (Bai et al 2011a), weak PARP inhibitors were shown to restore insulin expression (Ye et al 2006) and the deletion of Tankyrase 1 (PARP5a, TNK1) induced serum insulin levels (Yeh et al 2009).…”
Section: Parps In Regulating Central and Peripheral Organismal Metabomentioning
confidence: 99%
“…PARP1 and PARP2 activation were shown to be a key step in the development of insulin resistance (for review, see Bai and Cantó 2012). Hormones, such as insulin (Horvath et al 2008), estrogens (Mabley et al 2005;Jog and Caricchio 2013;Joshi et al 2014), androgens (Shimizu et al 2013), progesterone (Ghabreau et al 2004), artificial steroids, and vitamin D (Marton et al 2018b) can modulate the expression and activity of PARP1 and PARP2. Endocrine disruptors were also shown to modulate PARP activity (Chen et al 2013;Guerriero et al 2018).…”
Section: Parps In Regulating Central and Peripheral Organismal Metabomentioning
confidence: 99%
See 3 more Smart Citations